Perbedaan Kemandirian Belajar Ditinjau dari Gender dan Disposisi Matematis - Joko Sutrisno AB (Jurnal Inovasi Matematika, 2021)
This study aimed to analyze the differences in learning independence regarding gender and mathematical disposition in public junior high school students in Bandar Lampung. The research conducted was a survey study through the spread of questionnaires involving 355 students from 11 schools—data analysis using two-lane variance analysis. The results showed no difference in learning independence between male and female students. In terms of mathematical disposition, the average learning independence of students who had a higher high disposition than those who had low dispositions. This difference occurred between male students and female students. In students with low mathematical dispositions, it was known that the average independence of learning female students was higher than male students. Thus, to develop learning independence, students need to pay attention to students' gender and mathematical disposition characteristics to develop learning independence.